1991
DOI: 10.1159/000200743
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease in Indian Migrants in Fiji

Abstract: A pilot study to estimate the incidence of inflammatory bowel disease in Fiji is reported. Data from 1985 and 1986 for Indian migrants, Melanesians and other groups show the incidence of ulcerative colitis was 1.7/105/year, in Indians, 0.15/105/year in Melanesians and 1.4/105/year in others. The minimum incidence of Crohn’s disease is 0.14/105/year. Indians are at significantly greater risk than Melanesians of developing ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In Kurata et al. 's study, the prevalence rate of CD in Asian patients in California was low compared to that in whites and blacks 29 …”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In Kurata et al. 's study, the prevalence rate of CD in Asian patients in California was low compared to that in whites and blacks 29 …”
Section: Introductionmentioning
confidence: 86%
“…The high incidence rates amongst Indians or patients of South‐Asian descent are seen in many studies on migrants in the UK (Table 2). In one study from Fiji, migrant Indians had a higher prevalence of UC compared with the indigenous Melanesians, who belong essentially to the same racial stock as the Malays in South‐East Asia 29 . In Kurata et al.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding ethnic Indians in non‐Western countries outside of Asia, a study in Fiji found that Indians had a higher incidence of UC compared with the indigenous Melanesians 54 …”
mentioning
confidence: 99%
“…[36] Epidemiological studies have shown that CD tends to increase worldwide, particularly in industrialized countries with geographical variations. [711] Few reports have been published in the last three decades from the Kingdom of Saudi Arabia (KSA) and Kuwait indicating that it used to be a rare disease in this part of the world. [12–15] However, recent reports from various centers in the KSA have shown an increasing incidence.…”
mentioning
confidence: 99%